A mobile hemangioblastoma of the cauda equina: Case report and review of the literature - Luo, Haitao (J Spinal Cord Med, 2018)
Context: Cases of migratory spinal tumors have been reported since 1963. Most involve spinal schwannomas, which are benign tumors of the lining of nerve cells. We report a rare case of a mobile spinal hemangioblastoma, which is a type of benign vascular tumor. Findings: A 50-year-old man visited the hospital for painful swelling in his lower back. An MRI scan indicated that a lesion was at the L5 vertebral level. Two weeks later, however, an enhanced MRI showed that the lesion had migrated to the L4 vertebral level. During surgery, the location of the lesion remained consistent with the enhanced MRI reviewed. The histopathological diagnosis was hemangioblastoma. Conclusion: This is the first known report of a mobile spinal hemangioblastoma. Mobile spinal hemangioblastoma requires careful preoperative and intraoperative evaluation of its real-time location to avoid performing surgery at the wrong vertebral level.